PHYSICAL CULTURE AND SPORTS ACTIVITIES AS A FACTOR IN THE SOCIALIZATION OF STUDENTS IN THE SYSTEM OF HIGHER PROFESSIONAL EDUCATION - O. Borisov; K. Arov; O. Tsybulenko; D. Gladkikh; A. Kudrya (Вестник Северо-Кавказского федерального университета)
The article is devoted to the study of physical culture and sports activities in the system of higher professional education, which is a leading factor in the socialization of students and helps them to form and promote a healthy lifestyle and lifestyle culture outside of school hours, learn to make their own efforts to maintain and improve health, achieve life and training goals. Physical culture and sports activities are directly involved in the formation of the student's personality and at the same time sufficient motivation is created for them to physical self-education and self-improvement.